2002
DOI: 10.1074/jbc.m201307200
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptional Activation Function of the HIF-like Factor Requires Phosphorylation at a Conserved Threonine

Abstract: The hypoxia-inducible factor (HIF)-1␣ and the HIFlike factor (HLF) transcription factors are regulated at multiple levels including protein stabilization, nuclear import, and activation of transactivation, resulting in recruitment of coactivators such as the cAMP-response element-binding protein (CREB)-binding protein (CBP)/ p300 and SRC-1. During low oxygen tension these proteins modulate a network of genes that are necessary for angiogenesis, erythropopoiesis, and glycolysis. We report here that the C-termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 26 publications
(33 reference statements)
2
67
0
3
Order By: Relevance
“…Mutations such as R806A and Q810A had no significant effect on the transactivation function of C-TAD, whereas the mutants N807A and R816A showed an increased transactivation function at hypoxia when compared with the wild type C-TAD. The S805A mutation seemed to have no effect per se on the transactivation function of C-TAD either at normoxia or hypoxia, in agreement with a recent report where mutation of residue Ser 857 in HLF (corresponding to Ser 805 in mHIF-1␣) does not affect transactivation mediated by the C-TAD (36). The expression levels of all of the mutants tested in gene reporter assays were investigated by immunoblot analysis and proven to be very comparable (data not shown).…”
Section: Two Predicted ␣-Helices Within the C-tad Are Critical For Thsupporting
confidence: 78%
“…Mutations such as R806A and Q810A had no significant effect on the transactivation function of C-TAD, whereas the mutants N807A and R816A showed an increased transactivation function at hypoxia when compared with the wild type C-TAD. The S805A mutation seemed to have no effect per se on the transactivation function of C-TAD either at normoxia or hypoxia, in agreement with a recent report where mutation of residue Ser 857 in HLF (corresponding to Ser 805 in mHIF-1␣) does not affect transactivation mediated by the C-TAD (36). The expression levels of all of the mutants tested in gene reporter assays were investigated by immunoblot analysis and proven to be very comparable (data not shown).…”
Section: Two Predicted ␣-Helices Within the C-tad Are Critical For Thsupporting
confidence: 78%
“…For example, phosphorylation of hHIF-1a at Thr796 by casein kinase II was first postulated by Gradin et al 51 , and substitution of an aspartic acid residue at this position to mimic phosphorylation increased the interaction of the CAD with p300 within cells. It was subsequently shown that a peptide phosphorylated at this position could not be hydroxylated by FIH-1, 52 and the aspartic acid mutation significantly decreased hydroxylation efficiency in vitro.…”
Section: Other Modifications Affecting Hif-driven Transcriptionmentioning
confidence: 99%
“…We also addressed the question whether HIF-1 would be directly phosphorylated by CK2. Gradin et al 20 indicated that while T796 is phosphorylated in vivo and is a putative CK2 phosphorylation site, the TAD-C domain is not directly phosphorylated by CK2 in vitro. Computer analysis indicated that S551, S581, T700 and S787 in the human HIF-1a are also putative CK2 phosphorylation site with T700 having a higher score.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 However, the C-terminal transactivation domain (TAD-C) of HIF-1a is not directly phosphorylated by ERKs 19 but a negative charge on threonine 796, located in the C-terminal transactivation domain of HIF-1a, seems to be essential for the interaction with CBP/p300 and hence for the activity of HIF-1. 20 These results suggest that kinases other than ERK1/2 could be involved. The minimal consensus CK2 phosphorylation site is S/T-X-X-E/D and acidic amino acids around are favorable.…”
mentioning
confidence: 91%